TEACHING GRAMMAR - Raimberdiyeva Sabina Elyor qizi; Gaziyeva Saida Turgunovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT Teaching grammar is a crucial part of language education. Grammar provides the rules and structure that govern language usage, allowing learners to construct meaningful sentences and convey precise messages. This article explores the importance of grammar instruction in the classroom, the various methods used to teach grammar, and the challenges faced by both teachers and students. The study also emphasizes the need to balance explicit instruction with communicative practice to ensure grammar becomes an integral part of language proficiency.